GIS-MULTI CRITERIA ANALYSIS TO ENHANCE PLANNING JUDGEMENT FOR NEW TOWNSHIP DEVELOPMENT - Trihatmoko, Edy; Zen, Irina Safitri; Ibrahim, Illyani; Tampubolon, Dahlan (Jurusan Sosial Ekonomi, Fakultas Pertanian, Universitas Andalas, 2024)
Urban development is increasingly encroaching on hillsides, negatively impacting agriculture, particularly in developing countries like Malaysia, where flat land is scarce. To address this, the study aims to develop a GIS-based land suitability model that considers accessibility, environmental threats, and economic factors for optimal hillside development locations. Using multi-criteria decision analysis (MCDA) and the analytic hierarchy process (AHP) through Expert Choice software, key factors like accessibility, topography, land cover, and economics were analyzed. The study identifies Township 1, located 4.23 km northwest of UiTM, as the most suitable site for new development, considering current land use and proximity to key institutions. This model provides a framework for hillside development in Malaysia and other developing countries.